Design & planning - Shopware (Firm) (New Jersey : Shopware Productions, 2004)
This program will show students how homes get built on paper, what kinds of considerations drive many of the decisions and choices, and how to read the blueprints
Title from title screen
Teacher's guide online on www.shopware.usa.com
DVD format
Keywords: House construction; Architecture, Domestic -- Designs and plans; Building trades